Xanthogranulomatous salpingitis - pathological aspect of chronic pelvic inflammatory disease in a patient with sigmoid diverticulitis - Juneja, Sunil Kumar; Virk, Satpal Singh; Sharma, Anjali; Sood, Neena; Sood, Ajit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
A case of Xanthogranulomatous salpingitis in 55yrs old women with sigmoid diverticulitis is presented. Xanthogranulomatous inflammation is an uncommon form of chronic inflammation which affects various organs and is destructive in nature. This inflammatory process is characterized by massive infiltration of the tissues by lipid laden histiocytes admixed with lymphocytes, plasma cells and polymorphonuclear leucocytes. Pelvic inflammatory disease is the main etiology. This could have possibly resulted in xanthomatous process in our case leading to xanthogranulomatous salpingitis.